Illustration of a Measure to Combine Viral Suppression and Viral Rebound in Studies of HIV Therapy. (1st February 2015) - Edwards, Jessie K.; Cole, Stephen R.; Adimora, Adaora; Fine, Jason; Martin, Jeff; Eron, Joseph
Abstract : Abstract: Viral load is an important tool for assessing antiretroviral treatment efficacy. However, the most common viral load end point, virologic failure, may be flawed. We illustrate an alternative end point that estimates the average time patients spent suppressed before rebound in the AIDS Clinical Trials Group A5095 trial. Patients averaged 644 days suppressed in the 3-drug arm and 686 days suppressed in the 4-drug arm, for a difference of 42 days in favor of the 4-drug regimen (95% confidence interval: −11 to 96). These results agree with results using virologic failure as the end point but better emphasize the separate suppression and rebound processes. Abstract : Supplemental Digital Content is Available in the Text.